Dynamics and contribution of arbuscular mycorrhiza in culture systems with crop rotation - de Miranda, Jeanne Christine Claessen; Vilela, Lourival; de Miranda, Leo Nobre (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> Crop rotation and seasonal variations can promote quantitative and qualitative changes in the indigenous arbuscular mycorrhizal fungi population in the soil and arbuscular mycorrhiza establishment. These fungi dynamics were evaluated in the field, in a Red Latosol, in relation to cropping time, seasonal variation and rotation systems. The contribution of arbuscular mycorrhiza to the growth of andropogon grass and soybean, which were used in the systems, was evaluated in a greenhouse experiment using soil from the experimental area. The number of spores of the fungi increased in the cultivated soil. The spores number and percent root colonization varied according to cropping time, soil moisture, crops and rotation system and were, initially, higher under pasture. The number of genus and species increased according to cropping time and culture management and was higher under annual crops in rotation. The presence of these fungi in the soil contributed 53% and 95% to the growth of soybean and andropogon grass, respectively. Crops and cultivation system are crucial for the system's enrichment in arbuscular mycorrhiza.